Pengaruh Disiplin Kerja dan Fasilitas Kerja Terhadap Kinerja Karyawan PT Arina Multikarya Medan - Desvita, Bella; Ekawati, Yuni Andri; Wardani, Widia (Excellent, 2025)
The influence of Work Discipline and Work Facilities is reviewed in this study to examine the Employee Performance of PT Arina Multikarya Medan as partially and simultaneously. The data type of utilized is quantitative data. This study takes subjects from the population, i.e., company employees, a total of 30 person, where the population is used as a sample. Data gathered in this study uses interview techniques, making questionnaires, and documentation studies, namely obtained through books and journals. The data analysis technique uses multiple linear regression. The inferences of this study include: (1) Partially, the Work Discipline variable (X1) has a significant influence on the Employee Performance of PT Arina Multikarya Medan, as evidenced by the probability with a significance obtained of 0.000 (less than 0.05). (2) Partially, the Work Facilities variable (X2) has a significant influence on the Employee Performance of PT Arina Multikarya Medan, as evidenced by the probability with a significance obtained of 0.006. (3) Simultaneously, the variables Work Discipline (X1) and Work Facilities (X2) have a significant influence on Employee Performance at PT Arina Multikarya Medan, as proven by the F probability with a significance of 0.000. In addition, the determination of 0.900, which means 90 percent, indicates a very strong influence on the contribution of Employee Performance at PT Arina Multikarya Medan, given by the variables Work Discipline and Work Facilities.